Maternal phthalate exposure promotes allergic airway inflammation over 2 generations through epigenetic modifications - Jahreis, Susanne; Trump, Saskia; Eils, Roland (The journal of allergy and clinical immunology, 2018)
Background: Prenatal and early postnatal exposures to environmental factors are considered responsible for the increasing prevalence of allergic diseases. Although there is some evidence for allergy-promoting effects in children because of exposure to plasticizers, such as phthalates, findings of previous studies are inconsistent and lack mechanistic information. Objective: We investigated the effect of maternal phthalate exposure on asthma development in subsequent generations and their underlying mechanisms, including epigenetic alterations. Methods: Phthalate metabolites were measured within the prospective mother-child cohort Lifestyle and Environmental Factors and Their Influence on Newborns Allergy Risk (LINA) and correlated with asthma development in the children. A murine transgenerational asthma model was used to identify involved pathways. Results: In LINA maternal urinary concentrations of mono-n-butyl phthalate, a metabolite of butyl benzyl phthalate (BBP), were associated with an increased asthma risk in the children. Using a murine transgenerational asthma model, we demonstrate a direct effect of BBP on asthma severity in the offspring with a persistently increased airway inflammation up to the F2 generation. This disease-promoting effect was mediated by BBP-induced global DNA hypermethylation in CD4+ T cells of the offspring because treatment with a DNA-demethylating agent alleviated exacerbation of allergic airway inflammation. Thirteen transcriptionally downregulated genes linked to promoter or enhancer hypermethylation were identified. Among these, the GATA-3 repressor zinc finger protein 1 (Zfpm1) emerged as a potential mediator of the enhanced susceptibility for TH2-driven allergic asthma. Conclusion: These data provide strong evidence that maternal BBP exposure increases the risk for allergic airway inflammation in the offspring by modulating the expression of genes involved in TH2 differentiation through epigenetic alterations.